Highly sensitive and selective acute myocardial infarction detection using aptamer-tethered MoS2 nanoflower and screen-printed electrodes - Vasudevan, M. (Blackwell Publishing Ltd, 2020)
Acute myocardial infarction (AMI) is one of the leading causes of death worldwide. Cardiac troponin I (cTn1) is a commonly used biomarker for the diagnosis of AMI. Although there are various detection methods for the rapid detection of cTn1 such as optical, electrochemical, and acoustic techniques, electrochemical aptasensing techniques are commonly used because of their ease of handling, portability, and compactness. In this study, an electrochemical cTn1 biosensor, MoS2 nanoflowers on screen-printed electrodes assisted by aptamer, was synthesized using hydrothermal technique. Field emission scanning electron microscopy revealed distinct 2D nanosheets and jagged flower-like 3D MoS2 nanoflower structure, with X-ray diffraction analysis revealing well-stacked MoS2layers. Voltammetry aptasensing of cTn1 ranges from 10Â fM to 1Â nM, with a detection limit at 10Â fM and a sensitivity of 0.10Â nAÂ ÂµMâ1Â cmâ2. This is a â¼fivefold improvement in selectivity compared with the other proteins and human serum. This novel aptasensor retained 90 of its biosensing activity after 6 weeks with a 4.3 RSD and is a promising high-performance biosensor for detecting cTn1. Â© 2020 International Union of Biochemistry and Molecular Biology, Inc.